Haven't seen this before

Calculus Level 5

k = 0 k ! j = 0 k ( 2 j + 3 ) \sum_{k=0}^{\infty}\frac{k!}{\prod_{j=0}^{k}\left(2j+3\right)}

If the value of the expression above is of the form a + b π c a+b\pi^{c} , where a a and c c are integers and b b is a rational number, then find the value of 1 0 3 ( a 3 + b 3 + c 3 ) 10^{3}\left(a^{3}+b^{3}+c^{3} \right) .


The answer is 8875.00.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

5 solutions

Patrick Corn
Dec 10, 2019

The following identity is due to Lehmer (from a paper in the American Mathematical Monthly, 1985): m 1 ( 2 x ) 2 m m ( 2 m m ) = 2 x 1 x 2 sin 1 x . \sum_{m \ge 1} \frac{(2x)^{2m}}{m \binom{2m}{m}} = \frac{2x}{\sqrt{1-x^2}} \sin^{-1} x. Take the antiderivative of both sides (use integration by parts on the right, plug in 0 to get the integration constant); then plug in k = m + 1 k=m+1 : m 1 2 2 m x 2 m + 1 ( m ! ) 2 m ( 2 m + 1 ) ( 2 m ) ! = 2 x 2 ( sin 1 x ) 1 x 2 m 1 2 2 m x 2 m + 1 ( m 1 ) ! m ! ( 2 m + 1 ) ! = 2 x 2 ( sin 1 x ) 1 x 2 k 0 2 2 k + 2 x 2 k + 3 k ! ( k + 1 ) ! ( 2 k + 3 ) ! = 2 x 2 ( sin 1 x ) 1 x 2 k 0 2 k + 1 x 2 k + 3 k ! ( 2 4 ( 2 k + 2 ) ) ( 2 k + 3 ) ! = 2 x 2 ( sin 1 x ) 1 x 2 k 0 2 k + 1 x 2 k + 3 k ! j = 0 k ( 2 j + 3 ) = 2 x 2 ( sin 1 x ) 1 x 2 \begin{aligned} \sum_{m \ge 1} \frac{2^{2m} x^{2m+1} (m!)^2}{m(2m+1)(2m)!} &= 2x - 2(\sin^{-1} x)\sqrt{1-x^2} \\ \sum_{m \ge 1} \frac{2^{2m} x^{2m+1} (m-1)!m!}{(2m+1)!} &= 2x - 2(\sin^{-1} x)\sqrt{1-x^2} \\ \sum_{k \ge 0} \frac{2^{2k+2} x^{2k+3} k!(k+1)!}{(2k+3)!} &= 2x - 2(\sin^{-1} x)\sqrt{1-x^2} \\ \sum_{k \ge 0} \frac{2^{k+1} x^{2k+3} k! (2 \cdot 4 \cdots (2k+2))}{(2k+3)!} &= 2x - 2(\sin^{-1} x)\sqrt{1-x^2} \\ \sum_{k \ge 0} 2^{k+1} x^{2k+3} \frac{k!}{\prod_{j=0}^k (2j+3)} &= 2x - 2(\sin^{-1} x)\sqrt{1-x^2} \\ \end{aligned} Now plug in x = 1 / 2 , x=1/\sqrt{2}, to get 1 2 k 0 k ! j = 0 k ( 2 j + 3 ) = 2 2 2 2 ( sin 1 1 2 ) k 0 k ! j = 0 k ( 2 j + 3 ) = 2 2 ( π 4 ) = 2 π 2 . \begin{aligned} \frac1{\sqrt{2}} \sum_{k \ge 0} \frac{k!}{\prod_{j=0}^k (2j+3)} &= \frac2{\sqrt{2}} - \frac{2}{\sqrt{2}}\left(\sin^{-1} \frac1{\sqrt{2}} \right) \\ \sum_{k \ge 0} \frac{k!}{\prod_{j=0}^k (2j+3)} &= 2 - 2 \left(\frac{\pi}4\right) = 2-\frac{\pi}2. \end{aligned} So a = 2 , b = 1 / 2 , c = 1 a = 2, b = -1/2, c = 1 and the answer is 8875 . \fbox{8875}.

Syed Shahabudeen
Jan 19, 2020

The following sum mentioned in the question can be written in the form n = 2 ( n 2 ) ! 2 n n ! ( 2 n ) ! = n = 2 Γ ( n + 1 ) Γ ( n ) 2 n Γ ( 2 n + 1 ) ( n 1 ) \sum _{ n=2 }^{ \infty }{ \frac { \left( n-2 \right) !{ 2 }^{ n }n! }{ \left( 2n \right) ! } } =\sum _{ n=2 }^{ \infty }{ \frac { \Gamma \left( n+1 \right) \Gamma \left( n \right)2^{n} }{ \Gamma \left( 2n+1 \right) \left( n-1 \right) } } we know that 0 1 t x 1 ( 1 t ) y 1 d t = Γ ( x ) Γ ( y ) Γ ( x + y ) \int _{ 0 }^{ 1 }{ { t }^{ x-1 }{ \left( 1-t \right) }^{ y-1 }dt=\frac { \Gamma \left( x \right) \Gamma \left( y \right) }{ \Gamma \left( x+y \right) } } Therefore the sum in terms of the gamma function can be written as n = 2 2 n n 1 0 1 t n ( 1 t ) n 1 d t \sum _{ n=2 }^{ \infty }{ \frac { { 2 }^{ n } }{ n-1 } } \int _{ 0 }^{ 1 }{ { t }^{ n }{ \left( 1-t \right) }^{ n-1 }dt\; } on interchanging the sum and integral we get 0 1 1 1 t n = 2 ( 2 t ( 1 t ) ) n n 1 d t = 0 1 ( 2 t ln ( 1 2 t ( 1 t ) ) ) d t \int _{ 0 }^{ 1 }{ \frac { 1 }{ 1-t } \sum _{ n=2 }^{ \infty }{ \frac { { \left( 2t\left( 1-t \right) \right) }^{ n } }{ n-1 } dt\; = } } \int _{ 0 }^{ 1 }{ -\left( 2t\ln { \left( 1-2t\left( 1-t \right) \right) } \right) dt } since n = 2 ( 2 t ( 1 t ) ) n n 1 = 2 t ( 1 t ) ln ( 1 2 t ( 1 t ) ) \boxed{{ \sum _{ n=2 }^{ \infty }{ \frac { { \left( 2t\left( 1-t \right) \right) }^{ n } }{ n-1 } = } }{ -2t\left( 1-t \right) \ln { \left( 1-2t\left( 1-t \right) \right) } }} by applying Integration by parts , we will get 0 1 2 t ln ( 1 2 t ( 1 t ) ) d t = 2 π 2 \int _{ 0 }^{ 1 }{ -2t\ln { \left( 1-2t\left( 1-t \right) \right) } } dt=2-\frac { \pi }{ 2 } therefore a = 2 a=2 , b = 1 2 b=-\frac{1}{2} and c = 1 c=1 i.e 1 0 3 ( 8 1 8 + 1 ) = 8875 \boxed{10^{3}\left(8-\frac{1}{8}+1\right)=8875 }

Wesley Low
Dec 25, 2019

This solution will be heavily based on this paper by Renzo Sprugnoli.

Simplifying the summand gives us

k ! j = 0 k ( 2 k + 3 ) = k ! ( 2 k + 3 ) ! ! = 2 k + 1 k ! ( k + 1 ) ! ( 2 k + 3 ) ! = 2 k + 1 ( 2 k + 3 ) ( k + 1 ) ( 2 k + 2 k + 1 ) \frac { k! }{ \prod _{ j=0 }^{ k }{ \left( 2k+3 \right) } }=\frac { k! }{ \left( 2k+3 \right) !! } =\frac { { 2 }^{ k+1 }k!(k+1)! }{ \left( 2k+3 \right) ! } =\frac { { 2 }^{ k+1 } }{ \left( 2k+3 \right) \left( k+1 \right) \left( \begin{matrix} 2k+2 \\ k+1 \end{matrix} \right) }

After reindexing we get

k = 0 2 k + 1 ( 2 k + 3 ) ( k + 1 ) ( 2 k + 2 k + 1 ) = k = 1 2 k ( 2 k + 1 ) ( k ) ( 2 k k ) = k = 1 2 k k ( 2 k k ) 2 k + 1 ( 2 k + 1 ) ( 2 k k ) \sum _{ k=0 }^{ \infty }{ \frac { { 2 }^{ k+1 } }{ \left( 2k+3 \right) \left( k+1 \right) \left( \begin{matrix} 2k+2 \\ k+1 \end{matrix} \right) } } =\sum _{ k=1 }^{ \infty }{ \frac { { 2 }^{ k } }{ \left( 2k+1 \right) \left( k \right) \left( \begin{matrix} 2k \\ k \end{matrix} \right) } } =\sum _{ k=1 }^{ \infty }{ \frac { { 2 }^{ k } }{ k\left( \begin{matrix} 2k \\ k \end{matrix} \right) } } -\frac { { 2 }^{ k+1 } }{ \left( 2k+1 \right) \left( \begin{matrix} 2k \\ k \end{matrix} \right) }

We can further simplify the term on the right to get

k = 1 2 k + 1 ( 2 k + 1 ) ( 2 k k ) = k = 1 2 k + 1 ( k + 1 ) 2 2 ( k + 1 ) ( 2 k + 2 k + 1 ) = k = 1 2 k + 2 ( k + 1 ) ( 2 k + 2 k + 1 ) = 2 ( k = 1 2 k k ( 2 k k ) 1 ) \sum _{ k=1 }^{ \infty }{\frac { { 2 }^{ k+1 } }{ \left( 2k+1 \right) \left( \begin{matrix} 2k \\ k \end{matrix} \right) }}=\sum _{ k=1 }^{ \infty }{ \frac { { 2 }^{ k+1 } }{ \frac { { \left( k+1 \right) }^{ 2 } }{ 2\left( k+1 \right) } \left( \begin{matrix} 2k+2 \\ k+1 \end{matrix} \right) } } =\sum _{ k=1 }^{ \infty }{ \frac { { 2 }^{ k+2 } }{ \left( k+1 \right) \left( \begin{matrix} 2k+2 \\ k+1 \end{matrix} \right) } } =2\left( \sum _{ k=1 }^{ \infty }{ \frac { { 2 }^{ k } }{ k\left( \begin{matrix} 2k \\ k \end{matrix} \right) } } -1 \right) k = 1 2 k k ( 2 k k ) 2 k + 1 ( 2 k + 1 ) ( 2 k k ) = k = 1 2 k k ( 2 k k ) 2 ( k = 1 2 k k ( 2 k k ) 1 ) = 2 k = 1 2 k k ( 2 k k ) \sum _{ k=1 }^{ \infty }{ \frac { { 2 }^{ k } }{ k\left( \begin{matrix} 2k \\ k \end{matrix} \right) } } -\frac { { 2 }^{ k+1 } }{ \left( 2k+1 \right) \left( \begin{matrix} 2k \\ k \end{matrix} \right) } =\sum _{ k=1 }^{ \infty }{ \frac { { 2 }^{ k } }{ k\left( \begin{matrix} 2k \\ k \end{matrix} \right) } } -2\left( \sum _{ k=1 }^{ \infty }{ \frac { { 2 }^{ k } }{ k\left( \begin{matrix} 2k \\ k \end{matrix} \right) } } -1 \right)=2-\sum _{ k=1 }^{ \infty }{ \frac { { 2 }^{ k } }{ k\left( \begin{matrix} 2k \\ k \end{matrix} \right) } }

Now, let Z k {Z}_{k} denote 2 k ( 2 k k ) \frac { { 2 }^{ k } }{ \left( \begin{matrix} 2k \\ k \end{matrix} \right) } , and its generating function be Z ( t ) = k = 0 Z k t k Z\left( t \right) =\sum _{ k=0 }^{ \infty }{ { Z }_{ k } } { t }^{ k } . We can show that Z k + 1 = 2 k + 1 ( 2 k + 2 k + 1 ) = 2 2 ( k + 1 ) ( 2 k + 1 ) ( k + 1 ) 2 2 k ( 2 k k ) = k + 1 2 k + 1 2 k ( 2 k k ) = k + 1 2 k + 1 Z k { Z }_{ k+1 }=\frac { { 2 }^{ k+1 } }{ \left( \begin{matrix} 2k+2 \\ k+1 \end{matrix} \right) } =\frac { 2 }{ \frac { 2\left( k+1 \right) \left( 2k+1 \right) }{ { \left( k+1 \right) }^{ 2 } } } \frac { { 2 }^{ k } }{ \left( \begin{matrix} 2k \\ k \end{matrix} \right) } =\frac { k+1 }{ 2k+1 } \frac { { 2 }^{ k } }{ \left( \begin{matrix} 2k \\ k \end{matrix} \right) } =\frac { k+1 }{ 2k+1 } { Z }_{ k } 2 ( k + 1 ) Z k + 1 Z k + 1 = k Z k + Z k 2\left( k+1 \right) { Z }_{ k+1 }-{ Z }_{ k+1 }=k{ Z }_{ k }+{ Z }_{ k } 2 Z ( t ) Z ( t ) Z 0 t = t Z ( t ) + Z ( t ) 2{ Z'\left( t \right) }-\frac { Z\left( t \right) -{ Z }_{ 0 } }{ t } =tZ'\left( t \right) +Z\left( t \right) t ( 2 t ) Z ( t ) ( 1 + t ) Z ( t ) + 1 = 0 t\left( 2-t \right) { Z'\left( t \right) }-\left( 1+t \right) Z\left( t \right) +1=0

This differential equation can be solved by integrating factor to yield Z ( t ) = 2 2 t + 2 t ( 2 t ) 3 2 arcsin t 2 Z(t)=\frac { 2 }{ 2-t } +\frac { 2\sqrt { t } }{ { \left( 2-t \right) }^{ \frac { 3 }{ 2 } } } \arcsin { \sqrt { \frac { t }{ 2 } } }

Now, let W ( t ) = k = 1 W k t k = k = 1 2 k k ( 2 k k ) t k W(t)=\sum _{ k=1 }^{ \infty }{ { W }_{ k }{ t }^{ k } } =\sum _{ k=1 }^{ \infty }{ \frac { { 2 }^{ k } }{ k\left( \begin{matrix} 2k \\ k \end{matrix} \right) } { t }^{ k } } . To get W ( t ) W(t) from Z ( t ) Z(t) , we can observe that W k = Z k k {W}_{k}=\frac { { Z }_{ k } }{ k } . Knowing this, it is simply a matter of reindexing then integrating. We can thus define W ( t ) = 0 t Z ( z ) Z 0 z d z = 0 t ( 2 2 z + 2 z ( 2 z ) 3 2 arcsin z 2 ) 1 z d z = 2 t 2 t arcsin t 2 W(t)=\int _{ 0 }^{ t }{ \frac { Z\left( z \right) -{ Z }_{ 0 } }{ z } } dz=\int _{ 0 }^{ t }{ \frac { \left( \frac { 2 }{ 2-z } +\frac { 2\sqrt { z } }{ { \left( 2-z \right) }^{ \frac { 3 }{ 2 } } } \arcsin { \sqrt { \frac { z }{ 2 } } } \right) -1 }{ z } } dz=2\sqrt { \frac { t }{ 2-t } } \arcsin { \sqrt { \frac { t }{ 2 } } }

Going back to the original sum in question, it is obvious that W ( 1 ) = k = 1 2 k k ( 2 k k ) = 2 1 2 1 arcsin 1 2 = 2 arcsin 1 2 = π 2 W(1)=\sum _{ k=1 }^{ \infty }{ \frac { { 2 }^{ k } }{ k\left( \begin{matrix} 2k \\ k \end{matrix} \right) } }=2\sqrt { \frac { 1 }{ 2-1 } } \arcsin { \sqrt { \frac { 1 }{ 2 } } } =2\arcsin { \frac { 1 }{ \sqrt { 2 } } } =\frac { \pi }{ 2 }

Hence k = 0 k ! j = 0 k ( 2 j + 3 ) = 2 π 2 \sum _{ k=0 }^{ \infty }{ \frac { k! }{ \prod _{ j=0 }^{ k }{ \left( 2j+3 \right) } } } =\boxed{2-\frac { \pi }{ 2 }}

Thanks for that interesting paper!!!!

Aaghaz Mahajan - 1 year, 5 months ago
Hardik Kalra
Dec 28, 2019

There is a really beautiful approach to solve this problem. Here, I refer to the w a l l i s p r o d u c t \bold{wallis \space product} for odd powers of sin ( x ) \sin(x) (which you can pretty easily derive using the reduction formula), which is,

0 π 2 sin 2 n + 1 ( x ) d x = ( 2 n ) n ! ( 1 ) ( 3 ) ( 5 ) ( 2 n + 1 ) n N \int_0^{\frac{\pi}{2}}\sin^{2n+1}(x) dx = \frac{(2^n)n!}{(1)(3)(5)\dots(2n+1)} \space \forall \space n \space \in \space \mathbb N .

Using this, the above sum can be written as k = 1 1 ( 2 k ) ( k ) 0 π 2 sin 2 k + 1 ( x ) d x \sum_{k=1}^{\infty}\frac{1}{(2^k)(k)}\int_0^{\frac{\pi}{2}}\sin^{2k+1}(x) \space dx

Swapping the integral and summation,

0 π 2 sin ( x ) k = 1 ( sin 2 ( x ) 2 ) k k d x \int_0^{\frac{\pi}{2}}\sin(x)\sum_{k=1}^{\infty} \frac{(\frac{\sin^2(x)}{2})^k}{k} \space dx

If you take sin 2 ( x ) 2 = t \frac{\sin^2(x)}{2} = t , you note that the term ( sin 2 ( x ) 2 ) k k = t k 1 d t \frac{(\frac{\sin^2(x)}{2})^k}{k} = \int t^{k-1} dt .

The sum as of now is:

0 π 2 sin ( x ) k = 1 t k 1 d t d x \int_0^{\frac{\pi}{2}}\sin(x)\sum_{k=1}^{\infty} \int t^{k-1} dt \space dx

Swapping the inner integral and summation,

0 π 2 sin ( x ) k = 1 t k 1 d t d x \int_0^{\frac{\pi}{2}}\sin(x) \int \sum_{k=1}^{\infty} t^{k-1} dt \space dx

Because 0 < t < 1 x R 0 < t < 1 \space \forall \space x \space \in \space \mathbb R ,

0 π 2 sin ( x ) 1 / ( 1 t ) d t d x \int_0^{\frac{\pi}{2}}\sin(x) \int 1/(1-t) dt \space dx

After a couple of steps, this integral is:

0 π 2 sin ( x ) ln 1 + cos 2 ( x ) d x \int_0^{\frac{\pi}{2}}\sin(x) \ln{|1 + \cos^2(x)|} \space dx .

This can be easily solved using u-substitution to give the result 2 π 2 2 - \frac{\pi}{2}

Nice approach!!

Aaghaz Mahajan - 1 year, 5 months ago
Naren Bhandari
Dec 12, 2019

Let us denote the product P = j = 0 k ( 2 j + 3 ) = j = 1 k + 1 ( 2 j + 1 ) = ( 2 k + 3 ) ! ! P= \prod_{j=0}^{k} (2j+3)=\prod_{j=1}^{k+1} (2j+1)=(2k+3)!! The latter double factorial can further be expressed in terms of gamma function as ( 2 k + 3 ) ! ! = 2 k + 2 π Γ ( k + 5 2 ) = 2 k + 2 π ( ( 2 k + 4 ) ! π 2 2 k + 4 ( n + 2 ) ! ) (2k+3)!!=\dfrac{2^{k+2}}{\sqrt{\pi}}\Gamma\left(k+\dfrac{5}{2}\right)=\dfrac{2^{k+2}}{\sqrt{\pi}}\left(\dfrac{(2k+4)!\sqrt{\pi}}{2^{2k+4} (n+2)!}\right) and simplifying the latter expression we can get k = 0 k ! P 1 = k = 0 2 k ( k ! ) 2 ( 2 k + 1 ) ( 2 k + 3 ) ( 2 k ) ! = 1 2 k = 0 ( 1 2 k + 1 1 2 k + 3 ) 2 n ( 2 k k ) 1 \sum_{k=0}^{\infty}k !P^{-1} =\sum_{k=0}^{\infty} \dfrac{2^k(k!)^2}{(2k+1)(2k+3)(2k)!}=\dfrac{1}{2}\sum_{k=0}^{\infty} \left(\dfrac{1}{2k+1}-\dfrac{1}{2 k+3}\right)2^n\binom{2k}{k}^{-1} Since 2 ( sin 1 x ) 2 = k = 1 ( 2 x ) 2 k k 2 ( 2 k k ) 1 2(\sin^{-1}x)^2=\sum_{k=1}^{\infty}\dfrac{(2x)^{2k}}{k^2}\binom{2k}{k}^{-1} we want to get rid of k 2 k^2 term in the denominator as first we differentiate the function and we repeate once again and hence on multiplying by x x we can get 2 sin 1 x 1 x 2 = k = 1 ( 2 k ) 2 k k ( 2 k k ) 1 2 x d d x sin 1 x 1 x 2 = x sin 1 x + x 2 1 x 2 ( 1 x 2 ) 1 x 2 = k = 1 ( 2 x ) 2 k ( 2 k k ) 1 \begin{aligned} \dfrac{2\sin^{-1} x}{\sqrt{1-x^2}} & =& \sum_{k=1}^{\infty} \dfrac{(2k)^{2k}}{k}\binom{2k}{k}^{-1}\\2 x\dfrac{d}{dx}\dfrac{\sin^{-1}x}{\sqrt{1-x^2}} = \dfrac{x\sin^{-1}x+x^2\sqrt{1-x^2}}{(1-x^2)\sqrt{1-x^2}}&=&\sum_{k=1}^{\infty}(2x)^{2k}\binom{2k}{k}^{-1}\end{aligned} now we integrate with respect to x from 0 0 to 1 2 \frac{1}{\sqrt{2}} we get 1 2 k = 1 2 k 2 k + 1 ( 2 k k ) 1 = sin 1 x 1 x 2 x 0 1 2 = 1 2 ( π 2 1 ) \dfrac{1}{\sqrt 2}\sum_{k=1}^{\infty}\dfrac{2^k}{2k+1}\binom{2k}{k}^{-1} =\dfrac{\sin^{-1}x}{\sqrt{1-x^2}} -x{\LARGE|}_0^{\frac{1}{\sqrt 2}}=\dfrac{1}{\sqrt2}\left(\dfrac{\pi}{2}-1\right) and hence we have k = 0 2 k 2 k + 1 ( 2 k k ) 1 = π 2 \sum_{k=0}^{\infty} \dfrac{2^k}{2k+1}\binom{2k}{k}^{-1}=\dfrac{\pi}{2} similarly we multiply by x 2 x^2 and hnece on integrating from to 0 0 to 1 2 \frac{1}{\sqrt 2} . We get k = 1 2 k 2 k + 3 ( 2 k k ) 1 = 2 2 ( 3 π 4 2 13 6 2 ) k = 0 2 k 2 k + 3 ( 2 k k ) 1 = 3 π 2 4 \begin{aligned} \sum_{k=1}^{\infty} \dfrac{2^k}{2k+3} \binom{2k}{k}^{-1}& = 2\sqrt2\left(\dfrac{3\pi}{4\sqrt 2}-\dfrac{13}{6\sqrt2}\right)\\ \sum_{k=0}^{\infty}\dfrac{2^k}{2k+3}\binom{2k}{k}^{-1}& =\dfrac{3\pi}{2}-4\end{aligned} and hence k = 0 k ! ( j = 0 k ( 2 j + 3 ) ) 1 = 1 2 ( π 2 + 4 3 π 2 ) = 2 π 2 \sum_{k=0}^{\infty}k!\left(\prod_{j=0}^{k} (2j+3)\right)^{-1}=\dfrac{1}{2}\left(\dfrac{\pi}{2}+4-\dfrac{3\pi}{2}\right)=2-\dfrac{\pi}{2}

I left the working of integral since its not difficult to do. One can now easily derive the following more identities k 0 2 k 2 k + 1 ( 2 k k ) 1 = π 2 k 0 2 k 2 k + 3 ( 2 k k ) 1 = 3 π 2 4 k 0 2 k 2 k + 5 ( 2 k k ) 1 = 23 π 6 104 9 k 0 2 k 2 k + 7 ( 2 k k ) 1 = 91 π 10 2116 75 k 0 2 k 2 k + 9 ( 2 k k ) 1 = 1451 π 70 238912 3675 k 0 2 k 2 k + 11 ( 2 k k ) 1 = 5797 π 126 2863204 19845 \begin{aligned} \sum_{k\geq 0}\dfrac{2^k}{2k+1}\binom{2k}{k}^{-1} &=\frac{\pi}{2}\\ \sum_{k\geq 0}\dfrac{2^k}{2k+3}\binom{2k}{k}^{-1} & =\dfrac{3\pi}{2}-4\\\sum_{k\geq 0}\dfrac{2^k}{2k+5}\binom{2k}{k}^{-1} &=\dfrac{23\pi}{6}-\dfrac{104}{9}\\ \sum_{k\geq 0}\dfrac{2^k}{2k+7}\binom{2k}{k}^{-1} &=\dfrac{91\pi}{10}-\dfrac{2116}{75}\\\sum_{k\geq 0}\dfrac{2^k}{2k+9}\binom{2k}{k}^{-1} &=\dfrac{1451\pi}{70}-\dfrac{238912}{3675} \\ \sum_{k\geq 0}\dfrac{2^k}{2k+11}\binom{2k}{k}^{-1} & =\dfrac{5797\pi}{126}-\dfrac{2863204}{19845}\end{aligned} and soon. We can even solve using beta function.

I'm stupid

Kaden Johnson - 1 year, 3 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...